Collaboration between Islamic Education Teachers and Guidance Counsellors in Addressing Bullying at SMP Negeri 3 Kasihan - Alqodri; Hairiyah, Hairiyah; Susilowati, Ika Tri (el-Tarbawi, 2023)
Various cases of bullying happened in the educational system in Indonesia, from the elementary to high school levels. The increasing number of school bullying cases poses a challenge for guidance counsellors in addressing them. Therefore, collaboration between guidance counsellors and other teachers is essential, particularly with Islamic education teachers who play a similar role in shaping students' characters. The objective of this research is to describe how collaboration takes shape between Islamic education teachers and guidance counsellors in handling bullying at SMP Negeri 3 Kasihan. This study is qualitative and employs a field research approach. Findings of the study indicate that collaboration between Islamic education teachers and guidance counsellors in addressing bullying cases at SMP Negeri 3 Kasihan is formal collaboration in the form of preventive and corrective programs. Preventive programs include: first, displaying anti-bullying posters in the school area; second, collecting gadgets/phones to prevent cyberbullying within the school; third, bringing in experts or practitioners from outside the school; fourth, organizing cultural events. As for corrective programs, they include: first, implementing individual approaches for both the perpetrators and victims of bullying (call centre); second, imposing sanctions.